A Direct Proof of the Resonance‐Impaired Hydrogen Bond (RIHB) Concept. Issue 5 (20th December 2017) - Lin, Xuhui; Wu, Wei; Mo, Yirong
Abstract: The concept of resonance‐enhanced hydrogen bond (RAHB) has been widely accepted and applied as it highlights the positive impact of π‐conjugation on intramolecular H‐bonds. However, electron delocalization is directional and there is a possibility that π‐resonance goes from the H‐bond acceptor to the H‐bond donor, leading to a negative impact on H‐bonds. Here we used the block‐localized wavefunction (BLW) method which is a variant of ab initio valence bond (VB) theory and able to derive strictly electron‐localized structures self‐consistently, to quantify the interplay between H‐bond and π‐resonance in the terms of geometry, energetics and spectral properties. The comparison of geometrical optimizations with and without π‐resonance shows that conjugation can indeed either enhance or weaken intramolecular H‐bonds. We further experimented with various substituents attached to either the H‐bond acceptor and/or H‐bond donor side(s) to tune the H‐bonding strength in both directions. Abstract : By deactivating the π‐resonance using the block‐localized wavefunction (BLW) method, we quantitatively demonstrate that π‐resonance can either enhance or impair the intramolecular hydrogen bonding, depended on the direction of π‐electron density movement. Thus, apart from the popular resonance‐assisted hydrogen bond (RAHB), there is also resonance‐impaired hydrogen bond (RIHB).